(untitled) (Modern education and development, 2025)
The article states that intelligent agents, which are used in many fields, including robotics, medicine, finance, transportation, and e-commerce, are usually capable of self-learning and assimilating new knowledge, which increases their efficiency and adaptability. The article discusses the main types, technological foundations, applications, and future of intelligent agents.